Advances in ethanol autothermal reform for hydrogen gas production: a review (Research, Society and Development, 2020)
Concern about global warming and the high consumption of fossil fuels has led some countries to seek and invest in new energy sources that are efficient and less polluting. Among these alternatives, hydrogen fuel cells are a potential solution that can generate clean energy. Due to the industrial production of hydrogen being carried out by steam reforming of methane, which uses non-renewable raw material and is endothermic (resulting in high energy costs), the autothermal reform of ethanol has been presenting itself as an interesting technology, as it combines a renewable raw material with the reactions of reform (endothermic) and partial oxidation (exothermic), thus achieving energy self-sufficiency in the process of converting ethanol to hydrogen. Despite the various studies referring to the autothermal reform of ethanol, to our knowledge, no article has presented a detailed review of the main advances made in recent years for this process. Thus, this review presents the main results for the autothermal reform of ethanol, in recent years, in three main areas: Catalysts, Reactor Design and Modeling / Simulation. This work identified that the greatest advances have been made in the development of new catalysts and the design of reactors, while the modeling/simulation area still has few studies to efficiently describe the thermodynamics of the autothermal reform of ethanol.